2002
DOI: 10.1161/01.str.0000043072.76353.7c
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric MRI ISODATA Ischemic Lesion Analysis

Abstract: Background and Purpose-The purpose of this study was to show that the computer segmentation algorithm Iterative Self-Organizing Data Analysis Technique (ISODATA), which integrates multiple MRI parameters (diffusion-weighted imaging [DWI], T2-weighted imaging [T2WI], and T1-weighted imaging [T1WI]) into a single composite image, is capable of defining the ischemic lesion in a time-independent manner equally as well as the MRI techniques considered the best for each phase after stroke onset (ie, perfusion weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 27 publications
1
36
0
Order By: Relevance
“…Region-ofinterest analysis thereby inadvertently mixes the characteristics that one is trying to resolve. The complex temporal and spatial evolution of focal cerebral ischemia has prompted the use of more sophisticated analysis methods (Welch et al, 1995;Jiang et al, 1997;Carano et al, 1998Carano et al, , 2000Jacobs et al, 2000Jacobs et al, , 2001aWu et al, 2001;Mitsias et al, 2002) to stage stroke outcome. Multiparametric analysis using K-mean and Fuzzy c-mean clustering techniques have been used to classify ischemic tissue fate based on CBF index maps, T 2 and ADC maps in a rat stroke model (Carano et al, , 2000.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Region-ofinterest analysis thereby inadvertently mixes the characteristics that one is trying to resolve. The complex temporal and spatial evolution of focal cerebral ischemia has prompted the use of more sophisticated analysis methods (Welch et al, 1995;Jiang et al, 1997;Carano et al, 1998Carano et al, , 2000Jacobs et al, 2000Jacobs et al, , 2001aWu et al, 2001;Mitsias et al, 2002) to stage stroke outcome. Multiparametric analysis using K-mean and Fuzzy c-mean clustering techniques have been used to classify ischemic tissue fate based on CBF index maps, T 2 and ADC maps in a rat stroke model (Carano et al, , 2000.…”
Section: Introductionmentioning
confidence: 99%
“…This approach requires the number of tissue clusters to be assigned a priori, which is generally unknown during the evolution of cerebral ischemia. Jacobs et al (2001a) and Mitsias et al (2002) eloquently incorporated the iterative self-organizing data analysis algorithm (ISODATA) (Ball and Hall, 1965) for analyzing T 1 -, T 2 -and diffusion-weighted images in human stroke and found that the multiparametric ISODATA analysis outperformed analysis using any single parameter alone. This approach has also been applied to analyze T 1 -, T 2 -and diffusion-weighted images in an animal stroke models during the subacute and chronic phase (Jacobs et al, 2001b).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 6 compares the results of the ISODATA technique with those of the ANN. As shown in this figure the lesion areas in the ISODATA maps are clustered to different signatures (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Signatures range between one (corresponding to normal tissue) to twelve (corresponding to CSF or cavitated tissue).…”
Section: Resultsmentioning
confidence: 90%
“…Stop the gradient descent training at an appropriate point. 3. Add noise to the training patterns to smooth out the data points.…”
Section: Ann Optimization and Calculation Of The Ann Generalization Ementioning
confidence: 99%
See 1 more Smart Citation